2019
DOI: 10.1128/jvi.00841-19
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Interferon Alpha and Beta in Controlling Chikungunya Virus Replication and Modulating Neutrophil-Mediated Inflammation

Abstract: Type I interferons (IFNs) are key mediators of the innate immune response. Although members of this family of cytokines signal through a single shared receptor, biochemical and functional variation exists in response to different IFN subtypes. While previous work has demonstrated that type I IFNs are essential to control infection by chikungunya virus (CHIKV), a globally emerging alphavirus, the contributions of individual IFN subtypes remain undefined. To address this question, we evaluated CHIKV pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 68 publications
5
48
1
1
Order By: Relevance
“…Supporting this hypothesis, we showed that the level of CHIKV is less in the infected cells in the presence of recombinant IFNA2. Consistent with the previous research that has demonstrated that type I IFN signaling is essential to mitigate CHIKV-induced pathogenicity in mice (9,62). Furthermore, we found that the infiltration of neutrophils into the footpads of Il17ra −/− mice was significantly reduced compared to WT mice on day 6 p.i.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Supporting this hypothesis, we showed that the level of CHIKV is less in the infected cells in the presence of recombinant IFNA2. Consistent with the previous research that has demonstrated that type I IFN signaling is essential to mitigate CHIKV-induced pathogenicity in mice (9,62). Furthermore, we found that the infiltration of neutrophils into the footpads of Il17ra −/− mice was significantly reduced compared to WT mice on day 6 p.i.…”
Section: Discussionsupporting
confidence: 92%
“…Our results show the transcript levels of Isg-49 and Mx1 decrease in the presence of rIL-17A while increase in the presence of IL-17A neutralizing antibody during CHIKV infection, thus suggesting IL-17A directly or indirectly inhibits the ISG-49 and Mx1-mediated antiviral responses against CHIKV replication. Different IFN types may exert different functions during CHIKV infection, IFN-a limits early viral replication and dissemination; while IFN-b modulates neutrophil-mediated inflammation (62). Among IFN-a subtypes, IFN-a2 can be induced by Herpes Simplex Virus, Respiratory Syncytial Virus, and Newcastle Disease Virus (76).…”
Section: Discussionmentioning
confidence: 99%
“… Cook et al (2019) recently showed distinct but synergistic roles for IFN-α and β in controlling CHIKV replication and disease. While IFN-α acts in non-hematopoietic cell types, reducing replication and early dissemination of CHIKV, IFN-β has a substantial impact on pathogenesis, since it can limit neutrophil-mediated inflammation at the site of infection ( Cook et al, 2019 ).…”
Section: Virus–cell Interactionmentioning
confidence: 99%
“…Type I IFN signaling in non-hematopoietic cells controls viral infection and foot swelling during CHIKV infections [58,59] and can modulate immune cell recruitment and activation [38]. An early type I IFN response could activate certain immune cells subsets (e.g., such as NK cells [60]) that clear virus infection while limiting immune-mediated pathogenesis.…”
Section: Plos Pathogensmentioning
confidence: 99%